Empirical environmental justice research in hydrocarbon extraction areas: Examining current approaches outside the U.S. using a Mexican case study. (June 2019) - Hilburn, Andrew; Fry, Matthew
Highlights: Qualitative measures of oil/gas-related environmental justice outside the U.S. are lacking. We assess EJ in Mexico's Tampico-Misantla Basin using quantitative measures. Tests indicate lower marginalization for communities in buffers (1 km and 2.5 km) near wells. Presence of industry development in communities near wells help explain the lower marginalization but negative health and environmental effects persist. Application of quantitative EJ methods also should be accompanied with field analysis.